2011
DOI: 10.1093/molehr/gar049
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic events associated with endometrial and ovarian cancers are rare in endometriosis

Abstract: Endometriosis displays some features that resemble malignant processes, including invasive growth, resistance to apoptosis and distant implantation. The objective of this study was to investigate whether gene alterations that are frequent in endometrial and/or ovarian cancers contribute to the pathogenesis of endometriosis. Biopsies were obtained from ectopic endometriosis lesions from 23 patients with revised American Fertility Score stage 1 (n= 1), 2 (n= 10), 3 (n= 11) or 4 (n= 1) endometriosis. Six genes (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…16,17,39,40 However, given an estimated rate of malignant transformation for endometriosis close to 1%, 41 our results suggest that the presence of driver mutations alone is neither sufficient to drive the transformation of endometriosis nor indicative of likely progression to cancer. At least one study of a mouse model of endometriosis has already provided evidence that (subclonal) activating Kras mutations can sustain endometriosis but are not sufficient for malignant transformation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…16,17,39,40 However, given an estimated rate of malignant transformation for endometriosis close to 1%, 41 our results suggest that the presence of driver mutations alone is neither sufficient to drive the transformation of endometriosis nor indicative of likely progression to cancer. At least one study of a mouse model of endometriosis has already provided evidence that (subclonal) activating Kras mutations can sustain endometriosis but are not sufficient for malignant transformation.…”
Section: Discussionmentioning
confidence: 74%
“…However, the study of somatic mutations in endometriosis has been restricted largely to endometriosis with concurrent cancer. A small number of candidate-gene studies have examined benign (non–cancer-associated) ovarian endometriosis lesions; one study identified a KRAS mutation (p.G12C) in a single lesion, 16 and another identified PTEN mutations in 7 of 34 lesions (21%). 17 Immunohistochemical studies have also shown rare partial or complete immunohistochemical loss of ARID1A (as a proxy for ARID1A loss-of-function mutations) in lesions from ovarian and nonovarian endometriosis without concurrent cancer.…”
mentioning
confidence: 99%
“…The remaining 34 articles were screened in full texts. Then four articles were excluded for not being related to the TP53 gene (Campbell and Thomas, 2001;Hsieh et al, 2001;Silva et al, 2011;Stewart et al, 2013) and eight for not being case-control studies (Bayramoglu and Duzcan, 2001;Bischoff et al, 2002;Lahoti et al, 1996;Nakayama et al, 2001;Ribeiro Junior et al, 2009;Vercellini et al, 1994;Vestergaard et al, 2011;Xu et al, 2011); thus, a total of 22 articles was retained for data extraction. In the following procedures, three articles were excluded as duplicate data (Ammendola et al, 2008;Carvalho et al, 2010;Chang et al, 2002) and one article was regarded as two separate casecontrol studies because it reported two cohorts from different populations (Govatati et al, 2012).…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…However, recent studies deny the malignant or neoplastic potential of endometriosis, demonstrating that most endometriosis tissues are not monoclonal (Mayr, 2003). Furthermore, neither LOH of tumor suppressor genes, promoter methylation of oncogenes, nor oncogenic mutations of known tumor-related genes was frequently observed in the majority of the cases, further denying the neoplastic theory (Prowse, 2005;Vestergaard AL, 2011). In contrast with these results, a third approach (fluorescent in situ hybridization [FISH]) used to investigate chromosomal aberrations in endometriosis samples revealed a significantly elevated proportion of aneusomic (monosomic > trisomic) cells in endometriosis in multiple groups (Koerner, 2006) (Bischoff, 2002).…”
Section: Precancerous Lesions In Endometriosismentioning
confidence: 99%